2022
DOI: 10.1021/acsanm.2c02977
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4–Graphite Composites as a Microwave Absorber with Bimodal Microwave Absorption

Abstract: Microwave absorption in the low-frequency region is a major challenge in the development of carbon-based absorbers. Fe3O4–graphite composites with both low-frequency region and high-frequency region absorption were prepared through a facile solvothermal method. The electromagnetic properties and impedance matching characteristics of the samples were regulated by changing the dosage of graphite. Interestingly, an excellent bimodal microwave absorption (MA) performance was obtained when the molar ratio of iron a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 56 publications
1
9
0
1
Order By: Relevance
“…39 As shown in Figure 5c, the μ″(μ′) −2 f −1 of the 3400 nanocomposite remains almost 0 when the frequency is greater than 6 GHz owing to the dominant role of eddy current loss. 47 The variation in tan δ μ (tan δ μ = μ″/μ′) in Figure 5d is similar to that in μ″ in Figure 5b; therefore, the magnetic loss mechanism of the absorbing material is mainly afforded by the eddy current effect. 11 Noteworthily, the tan δ ε value of the 3400 nanocomposite is much higher than that of the 3400 nanocomposite (Figure 4c), indicating that dielectric loss plays a more important role than the magnetic loss in microwave absorption performance.…”
Section: ■ Experimental Sectionsupporting
confidence: 55%
See 1 more Smart Citation
“…39 As shown in Figure 5c, the μ″(μ′) −2 f −1 of the 3400 nanocomposite remains almost 0 when the frequency is greater than 6 GHz owing to the dominant role of eddy current loss. 47 The variation in tan δ μ (tan δ μ = μ″/μ′) in Figure 5d is similar to that in μ″ in Figure 5b; therefore, the magnetic loss mechanism of the absorbing material is mainly afforded by the eddy current effect. 11 Noteworthily, the tan δ ε value of the 3400 nanocomposite is much higher than that of the 3400 nanocomposite (Figure 4c), indicating that dielectric loss plays a more important role than the magnetic loss in microwave absorption performance.…”
Section: ■ Experimental Sectionsupporting
confidence: 55%
“…The magnetic loss mechanisms are eddy current loss, domain wall displacement, and hysteresis, , among which the eddy current effect is the main loss mechanism, and the other two have little influence; therefore, the value of μ″(μ′) −2 f –1 is consistent with the change in frequency . As shown in Figure c, the μ″(μ′) −2 f –1 of the 3400 nanocomposite remains almost 0 when the frequency is greater than 6 GHz owing to the dominant role of eddy current loss . The variation in tan δ μ (tan δ μ = μ″/μ′) in Figure d is similar to that in μ″ in Figure b; therefore, the magnetic loss mechanism of the absorbing material is mainly afforded by the eddy current effect .…”
Section: Resultsmentioning
confidence: 73%
“…The storage of the EM wave, interfacial polarization, and dipolar polarization is essentially connected to ε r ′. 61 The PU dipoles get activated in the presence of an incident EM wave and experience dipolar polarization, which oscillates according to the frequency of the applied EM wave. The localized heterogeneous system within the synthesized nanocomposite is caused by the interaction between CF, CNT, and PU, which results in interfacial polarization.…”
Section: Resultsmentioning
confidence: 99%
“…The primary factor like electrical conductivity and complex microwave permittivity is responsible for the overall storage and absorption of the EM wave in the nanocomposite structure. The storage of the EM wave, interfacial polarization, and dipolar polarization is essentially connected to ε r ′ . The PU dipoles get activated in the presence of an incident EM wave and experience dipolar polarization, which oscillates according to the frequency of the applied EM wave.…”
Section: Results and Discussionmentioning
confidence: 99%
“…EMI SE materials typically attenuate electromagnetic energy through conduction loss, dielectric loss, and magnetic loss. For nonmagnetic carbon-based dielectric loss materials, their excellent dielectric loss ability can enable rapid attenuation of electromagnetic wave energy as it propagates within the material. But the material itself cannot attenuate electromagnetic energy infinitely, and its absorption bounds will limit the upper bounds of EMI SE performance improved by multilayer design. , To further explain the contribution of the multilayer structure to EMI SE performance, the average SE T , SE R , and SR A of composite materials with different layers at 0.3 mm thickness are compared in Figure d. It can be observed that with the increase of the number of layers, its corresponding electromagnetic wave reflection value SE R has no obvious upward trend, while its electromagnetic absorption value SE A increases step by step, indicating that the multilayer structure is conducive to the multiple reflection and absorption of electromagnetic waves, thus improving the basic shielding mechanism of its EMI SE performance.…”
Section: Resultsmentioning
confidence: 99%